Tragic Bodies : Edges of the Human in Greek Drama - Worman, Nancy (Bloomsbury Publishing Plc, 2020)
Cover page -- Halftitle page -- Series page -- Title page -- Copyright page -- Epigraph -- Dedication -- CONTENTS -- ACKNOWLEDGMENTS -- PROLOGUE SKIN TO SKIN IN GREEK TRAGEDY -- 1. Figuration, Embodiment, and Semiotic Materialities -- 2. Tragic Aesthetics -- 3. A Net the Gods Made -- 4. Setting the Scene -- CHAPTER 1 TOUCHING OEDIPUS: PROXIMITIES, CONTACT, AND AFFECTIVE INTIMACIES -- 1. Sensing Bodies -- 2. Witnessing and Handling Bodies in Pain -- 3. Oedipal Proxemics and Touching -- CHAPTER 2 THE SIBLING HAND: MANUAL EROTICS AND VIOLENCE -- 1. Hands-on Family -- 2. Killing Versus Loving Hands (Aeschylus to Sophocles) -- 3. Siblings Hand-to-Hand (Euripides) -- 4. Other Manual Menaces -- CHAPTER 3 FAMILIAL COVERINGS: SKIN, CLOAKS, AND OTHER OUTERWEAR -- 1. Parental Carapaces -- 2. Spousal Mantles -- 3. Racialized Carapaces -- 4. Shields, Pelts, and Similar Shells -- CHAPTER 4 STRANGE CONTAINERS: BODIES AND OTHER TRAGIC VESSELS -- 1. "Material" Edges -- 2. "Human" Vessels: Jar, Coffin, Tomb -- 3. Inside Out -- CHAPTER 5 BODILY ALTERATIONS: UNDRESS, PROSTHESIS, AND ASSEMBLAGE -- 1. Fleshly Extensions -- 2. Female Assemblages and "Nudity" -- 2. Captive and Mourning Assemblages -- 3. Other Familial Groupings -- CHAPTER 6 MYSTERIOUS OBJECTS: CORPSES, GHOSTS, STATUES -- 1. Creatures and Demons in Aeschylus -- 2. Ghosts and Eerie Doubles -- 3. Suppliant Bodies and/as Statues -- 4. The Undead -- FINAL SCENES: BEYOND THE HUMAN -- BIBLIOGRAPHY -- INDEX LOCORUM -- GENERAL INDEX.